Hubungan Citra Merek dan Kesesuaian Harga dengan Keputusan Pembelian pada Brand Streetwear Lokal - Nindri Widianingsih; Halimah Zahrah (Indo Publishing, 2026)
The development of the fashion industry in Indonesia, especially in Bandung, is very rapid every year, many fashion brands are emerging. One strategy to maintain its existence is by paying attention to brand image and price. This study aims to analyze the influence of brand image and price on purchasing decisions for WHSTL Official products in Bandung. The research method used is quantitative with data collected through questionnaires to 150 respondents who have purchased the product. The data analysis technique used multiple linear regression with the help of SPSS 27. The results showed that price has a positive and significant effect on purchasing decisions. Conversely, brand image has a negative and significant effect, which indicates that current brand perceptions do not support purchase intentions. Simultaneously, brand image and price have a significant effect on purchasing. This study suggests that WHSTL Official should focus its strategy on competitive pricing and reevaluate brand management to change consumer perceptions into positive purchasing behavior.